A Novel Algorithm for Redundant Data Filtering in WSN and RFID Integrated Networks (Nexo Revista Científica, 2022)
Wireless sensor networks (WSN) and radio frequency identification (RFID) are base technologies employed in decentralised dynamic environments. In the hybrid network formed by integrating RFID and WSN, RFID data can be used applying WSN protocols for multi-hop communications. However, RFID data contain excessive duplication, which increases time delay and energy consumption, resulting in wastage of different resources. There exist four popular RFID–WSN integration architectures: hierarchical RFID-sensor topology, network RFID-sensor topology, reader-sensor nodes topology, and mixed topology. In this paper, we propose a new plan for a WSN–RFID integrated network. The entire network is divided into clusters, and the clustering hierarchical routing algorithm is employed to send data from the head nodes to the base station. Further, we propose two algorithms to overcome redundant data on the hybrid network. Our simulation results demonstrate that the proposed method reduces redundant data and processing time compared with existing methods.